The A - B - C for a Healthy Back (Fiep Bulletin - online, 2015)
For the gymnastics light clothes are to be worn. In Summer the movements can be performed in the open air, in winter in a well ventilated room. In the beginning each movement is executed 5 time and the whole programme is performed at least once a day